Antihyperlipidemic Activity of Ethanolic Extract of Celery Stem on Rats Rattus norvegicus - Dawood Sharief, S (International Journal of Pharmaceutical & Biological Archive, 2014)
Antihyperlipidemic Activity of Ethanolic Extract of Celery Stem on Rats Rattus norvegicus